Locomotory Adaptations in 3D Humerus Geometry of Xenarthra: Testing for Convergence - Serio, Carmela; Raia, Pasquale; Meloro, Carlo (Frontiers in Ecology and Evolution, 2020)
Three-dimensional models of fossil bones are increasingly available, thus opening a novel frontier in the study of organismal size and shape evolution. We provide an example on how photogrammetry can be combined with Geometric Morphometrics (GMM) techniques to study patterns of morphological convergence in the mammalian group of Xenarthra. Xenarthrans are currently represented by armadillos, sloths and anteaters. However, this clade showed an incredibly diverse array of species and ecomorphotypes in the fossil record, including gigantic ground sloths and glyptodonts. Since the humerus is a weight-bearing bone in quadrupedal mammals and its morphology correlates with locomotor behaviour, it provides an ideal bone to gain insight into adaptations of fossil species. A 3D sample of humerii belonging to extant and fossil Xenartrha allowed us to identify a significant phylogenetic signal and a strong allometric component in the humerus shape. Although no rate shift in the evolution of humerus shape was recorded for any clade, fossorial and arboreal species humerii did evolve at significantly slower and faster pace, respectively, than the rest of the Xenarthran species. Significant evidence for morphological convergence found among the fossorial species and between the two tree sloths genera explain these patterns. These results suggest that the highly specialized morphologies of digging taxa and tree sloths represent major deviations from the plesiomorphic Xenarthran body plan, and evolved several times during the history of the group.